Two-Year-Olds’ Symbolic Use of Images Provided by a Tablet: A Transfer Study - Jauck, Daniela; Peralta, Olga (Frontiers in Psychology, 2019)
Touch screen devices are nowadays part of everyday life and parents and educators assume that young children use their images in a symbolic way. This research aims at replicating and expanding a previous one that reported that, contrary to expectations and to studies with printed or video images, 2-year-old children used the images on a tablet to retrieve a hidden object (Search), but not to communicate the location of an object they have observed being hidden (Point). In this research we carried out a transfer study comparing the performance of an Experimental (Search-Point) and a Control group (Point-Point). We found that the Experimental group outperformed the Control group, and that the successful symbolic previous experience gained in the Search tasks was transferred to the Point task, task which two-year-olds otherwise fail.